The Enigmatic Function of Chandelier Cells - Woodruff, Alan R.; Anderson, Stewart A.; Yuste, Rafael (Frontiers in Neuroscience, 2010)
Chandelier (or axo-axonic) cells are one of the most distinctive GABAergic interneurons in the brain. Their exquisite target specificity for the axon initial segment of pyramidal neurons, together with their GABAergic nature, long suggested the possibility that they provide the ultimate inhibitory control of pyramidal neuron output. Recent findings indicate that their function may be more complicated, and perhaps more interesting, than initially believed. Here we review these recent developments and their implications. We focus in particular on whether chandelier cells may provide a depolarizing, excitatory effect on pyramidal neuron output, in addition to a powerful inhibition.